Polydactyly in the aborigines of pre-Columbian Peru - Paico-Vílchez, Emiliano (2024)
In this article the authors highlight the presence of polydactyly among the aborigines of ancient Peru. They show photographs of splendid ceramics recovered from tombs of ancient Peruvian cultures, which are testimony of the presence of polydactyly in the ancient aborigines; that is, more than five fingers or toes, unilateral or bilateral.